High-transparency light-color heat-resistant copolyester and preparation method thereof

By adding licorice antioxidants and rosemary extracts in the preparation process of copolyester, the crystal structure of copolyester is adjusted, and the problems of low transparency and poor color at high temperatures are solved, and the light transmittance and heat resistance are improved. Efficient color and performance improvements are achieved.

CN119119436AActive Publication Date: 2024-12-13WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411507466.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-13
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing transparent heat-resistant copolyesters have low transparency, high haze and poor thermal stability at high temperatures, which are prone to side reactions to produce color, affecting the light transmittance and color of the product.

Method used

During the preparation of copolyester, licorice antioxidants and rosemary extract composition are added for esterification or transesterification reaction, adjust the crystal structure of copolyester, weaken the influence of side reactions at high temperatures, and improve light transmittance and color.

Benefits of technology

The light transmittance and heat resistance of copolyester is significantly improved, haze and chromatic aberration is reduced, and the tensile strength and chromatic aberration of injection molded splines and optical samples are maintained well at high temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides high-transparency light-color heat-resistant copolyester and a preparation method thereof. The preparation method comprises the following steps: carrying out esterification on dibasic acid and dihydric alcohol, and / or carrying out transesterification on dimethyl ester of the dibasic acid and dihydric alcohol to obtain an esterified substance and / or a transesterified substance; carrying out a pre-polycondensation reaction on the esterified product and / or the ester exchange product to obtain a prepolymer; and performing final polycondensation reaction on the prepolymer to obtain the target copolyester. According to the method, a licorice antioxidant and rosemary extract composition is added for esterification and / or transesterification. According to the method, the crystal structure of a copolyester reactant can be adjusted, the light transmittance of the copolyester can be improved, the haze can be reduced, the effect of side reaction at high temperature can be weakened, and the color production problem can be weakened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyesters, and particularly relates to a highly transparent, light-colored, heat-resistant copolyester and a preparation method thereof. Background Art

[0002] Poly(1,4-cyclohexanedimethanol terephthalate) (PCT for short) is a transparent heat-resistant copolyester resin with excellent performance. It is obtained by esterification-polycondensation reaction of terephthalic acid (PTA) and 1,4-cyclohexanedimethanol (CHDM) or transesterification-polycondensation reaction of dimethyl terephthalate (DMT) and 1,4-cyclohexanedimethanol (CHDM). PCT has the characteristics of high melting point and fast crystallization rate, and the material is opaque. In order to reduce the crystallization rate and melting point of PCT and obtain colorless, transparent and heat-resistant materials, it is usually copolymerized with other diol monomers, such as 2,2,4,4-tetramethyl-1,3-cyclobutanediol (CBDO), neopentyl glycol (NPG), and ethylene glycol (EG), which can inhibit PCT crystallization and obtain transparent products. Among them, the copolyester obtained by copolymerization with CBDO is not only transparent, but also has a high glass transition temperature and good impact resistance. It has broad applications in water cups, electronic cigarettes, small household appliances and other fields.

[0003] The difference in crystal structure on a microscopic scale during the melt polycondensation of copolyesters is one of the reasons that affect the light transmittance of copolyesters. In addition, due to insufficient thermal stability, side reactions are prone to coloration at high temperatures, affecting the color of the product. During the synthesis of CN101300285A copolyester, without the addition of stabilizers, the melt surface is very unstable, and excessive foaming and frothing cause the melt to have a high porosity. The copolyester in CN101300285A is prone to yellowing, and even with the addition of stabilizers, a light yellow product may be obtained.

[0004] In summary, the current transparent heat-resistant copolyester still has problems of low light transmittance and poor color that need to be solved urgently. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a highly transparent, light-colored, heat-resistant copolyester in view of the problems that the existing copolyester has low transparency and high haze at high temperatures, poor thermal stability, and is prone to side reaction coloration. The method can adjust the crystal structure of the copolyester reactant, improve the light transmittance of the copolyester and reduce the haze, and can also reduce the effects of side reactions at high temperatures and reduce the coloration problem.

[0006] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a copolyester, the method comprising the following steps:

[0008] S1: esterification of a dibasic acid with a diol, and / or transesterification of a dimethyl ester of a dibasic acid with a diol to obtain an esterified product and / or a transesterified product;

[0009] S2: the esterification product and / or the transesterification product are subjected to a pre-condensation reaction to obtain a prepolymer;

[0010] S3: The prepolymer undergoes a final polycondensation reaction to obtain the target copolyester;

[0011] Wherein, a liquorice antioxidant and a rosemary extract composition are added to S1 to carry out esterification and / or transesterification reaction.

[0012] The inventors adjusted the copolyester crystal structure by adding a licorice antioxidant and a rosemary extract composition during the esterification or transesterification stage of the reaction, and at the same time weakened the side reactions at high temperatures during the synthesis of the copolyester, thereby achieving the purpose of improving light transmittance, color, heat resistance and processing performance.

[0013] In one embodiment of the present invention, the dibasic acid in the dibasic acid or the dimethyl ester of the dibasic acid in S1 is a C6-C20 dibasic acid, preferably one or more of terephthalic acid or its dimethyl ester, isophthalic acid or its dimethyl ester, phthalic acid or its dimethyl ester, biphenyl dicarboxylic acid or its dimethyl ester, naphthalene dicarboxylic acid or its dimethyl ester, furandicarboxylic acid or its dimethyl ester, thiophenedicarboxylic acid or its dimethyl ester, and cyclohexanedicarboxylic acid or its dimethyl ester, more preferably terephthalic acid or its dimethyl ester, and / or isophthalic acid or its dimethyl ester.

[0014] In one embodiment of the present invention, the diol described in S1 is a C2-C20 aliphatic diol and / or aromatic diol, preferably 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, isosorbide, ethylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 1,2-propylene glycol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,4-pentanediol, 1,5-pentanediol, neopentyl glycol, 3- One or more of methyl 1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, diethylene glycol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, spiroglycol, tricyclodecane dimethanol, more preferably 1,4-cyclohexanedimethanol and / or 2,2,4,4-tetramethyl-1,3-cyclobutanediol; preferably, the molar ratio of the diol to the diacid or the diester of the diacid is (1.1-1.5):1, preferably (1.2-1.4):1.

[0015] In one embodiment of the present invention, the licorice antioxidant in S1 is licorice flavonoids and / or glycyrrhizin, and the rosemary extract is carnosic acid and / or carnosin; preferably, the mass ratio of the licorice antioxidant to the rosemary extract is (0.1-10):1, preferably (0.5-3):1; preferably, the licorice antioxidant and rosemary extract composition is 100-300ppm of the total mass feed amount of the diol and the diacid and / or the diester of the diacid, preferably 200-300ppm.

[0016] In one embodiment of the present invention, S1 adds a catalyst; preferably, the catalyst is dibutyltin oxide, dimethyltin oxide, monobutyltin triisooctoate, dibutyltin dimethoxy, stannous octoate, stannous oxalate, dibutyltin diacetate, dibutyltin dilaurate, tetrabutyl titanate, isopropyl titanate, ethylene glycol titanium, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, preferably dibutyltin oxide and / or tetrabutyl titanate; preferably, the catalyst is 200 to 500 ppm of the total mass feed of the diol and the diacid and / or the diester of the diacid, preferably 300 to 400 ppm. The above-mentioned additives and their dosages are the commonly used selections and dosages in this field.

[0017] In one embodiment of the present invention, S1 adds a heat stabilizer; preferably, the heat stabilizer is a phosphate compound, preferably an alkyl phosphate and / or an aryl phosphate, more preferably triphenyl phosphate and / or triethyl phosphate; preferably, the heat stabilizer is 300 to 600 ppm, preferably 300 to 400 ppm, of the total mass feed amount of the diol and the diacid and / or the diester of the diacid. The above-mentioned auxiliary agent and its dosage are the commonly used selection and dosage in this field.

[0018] In one embodiment of the present invention, the reaction temperature of S1 is 190-240°C, preferably 210-230°C, and the reaction time is 120-240 min, preferably 150-180 min.

[0019] In one embodiment of the present invention, the reaction temperature in S2 is 240-260°C, preferably 240-250°C, the absolute reaction pressure is 1-3 kPa, preferably 1-2 kPa, and the reaction time is 30-60 min, preferably 40-50 min.

[0020] In one embodiment of the present invention, the reaction temperature in S3 is 250-270°C, preferably 260-265°C, the absolute pressure of the reaction is less than 100 Pa, preferably less than 50 Pa, and the reaction time is 120-300 min, preferably 150-210 min.

[0021] Another object of the present invention is to provide a copolyester.

[0022] A copolyester is prepared by the above-mentioned preparation method, and the copolyester is a highly transparent, light-colored, heat-resistant copolyester.

[0023] In one embodiment of the present invention, the intrinsic viscosity of the copolyester is greater than 0.6 dL / g, the tensile strength of the injection molded strip is greater than 40 MPa, the light transmittance of the optical sample is greater than 90%, the haze is less than 1%, the color difference L value is greater than 90, the absolute value of the a value is less than 1, and the absolute value of the b value is less than 1; after the pellets are heated at 260-280°C for 10 minutes, the tensile strength of the injection molded strip is less than 2 MPa, and the color difference Δb value of the optical sample is less than 0.2.

[0024] Compared with the prior art, the positive effects of the technical solution of the present invention are:

[0025] (1) The preparation method of the present invention can play a role in adjusting the crystal structure of the copolyester and improving the light transmittance of the copolyester.

[0026] (2) The preparation method of the present invention can reduce the effect of side reactions at high temperatures during the synthesis of copolyester and improve the hue of the copolyester;

[0027] (3) The copolyester prepared by the preparation method of the present invention has good heat resistance and processing performance. After heating at 260-280° C. for 30 minutes, the tensile strength and color difference of the injection molded specimens are maintained well. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific examples. It should be noted that the examples are only used to illustrate the present invention and do not constitute a limitation on the scope of protection claimed for the present invention.

[0029] The raw materials of diol, dibasic acid or its dimethyl ester, catalyst, heat stabilizer, licorice antioxidant and rosemary extract composition are all commercially available and have analytical purity. Dimethyl terephthalate, terephthalic acid, dimethyl thiophenedicarboxylate, cyclohexanedicarboxylic acid, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, ethylene glycol, isosorbide, spirodiol and tricyclodecane dimethanol were purchased from Beijing Inokai Technology Co., Ltd. with a purity of 99%, dibutyltin oxide, tetrabutyl titanate, ethylene glycol titanium, zinc acetate, triphenyl phosphate and triethyl phosphate were purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 98%, and licorice flavonoids, glycyrrhizin, carnosic acid and carnosol were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a purity of 98%.

[0030] The devices and methods used in the present invention are commonly used in the art.

[0031] Intrinsic viscosity: The intrinsic viscosity of the sample at 25°C was measured using a Nanjing Tenghui Ubbelohde viscometer. The solvent was phenol / tetrachloroethane (mass ratio w / w=3 / 2) and the sample concentration was 0.005 g / mL.

[0032] Mechanical properties: Tensile strength: Dumbbell-shaped specimens with a width of 4 mm and a thickness of 2 mm were prepared using a HaakeMiniJet II micro injection molding machine and tested using a mechanical testing machine (Instron 5960) at a tensile speed of 50 mm / min.

[0033] Optical properties: A HaakeMiniJet II micro-injection molding machine was used to prepare discs with a diameter of 25 mm and a thickness of 1.5 mm; a desktop spectrophotometer CS-821N was used to measure the transmittance and haze indexes: transmittance and haze H. Color difference index: L / a / b (representing brightness or black and white, green / red, and blue / yellow, respectively).

[0034] Example 1

[0035] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.38g of dibutyltin oxide, 0.57g of triphenyl phosphate, 0.02g of glycyrrhizin and 0.17g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 240°C for 120min. The reactor was then evacuated to 3kPa, reacted at 240°C for 60min, and then evacuated to 50Pa, and reacted at 250°C for 300min to obtain copolyester 1. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.641dL / g, a tensile strength of an injection molded sample of 43MPa, a transmittance of 92%, a haze of 0.7%, a color difference L value of 93, a value of -0.5, and an absolute value of b value of 0.7. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 42 MPa and the color difference b value of the optical sample was 0.8.

[0036] Example 2

[0037] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.95g of dibutyltin oxide, 1.14g of triphenyl phosphate, 0.52g of glycyrrhizin and 0.05g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 190°C for 240min. The reactor was then evacuated to 1kPa, reacted at 260°C for 30min, and then evacuated to 100Pa, reacted at 270°C for 120min to obtain copolyester 2. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained, with an intrinsic viscosity of 0.648dL / g, a tensile strength of an injection molded sample of 44MPa, a transmittance of 92%, a haze of 0.6%, a color difference L value of 94, a value of -0.5, and an absolute value of b value of 0.7. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 43 MPa and the color difference b value of the optical sample was 0.8.

[0038] Example 3

[0039] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide, 0.57g of triphenyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 3. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.652dL / g, a tensile strength of an injection molded sample of 46MPa, a transmittance of 93%, a haze of 0.5%, a color difference L value of 95, a value of -0.3, and an absolute value of b value of 0.5. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 45 MPa and the color difference b value of the optical sample was 0.5.

[0040] Example 4

[0041] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.76g of dibutyltin oxide, 0.76g of triphenyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 230°C for 180min. The reactor was then evacuated to 2kPa, reacted at 250°C for 50min, and then evacuated to 50Pa, and reacted at 265°C for 210min to obtain copolyester 4. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.651dL / g, a tensile strength of an injection molded sample of 45MPa, a transmittance of 92%, a haze of 0.6%, a color difference L value of 94, a value of -0.3, and an absolute value of b value of 0.6. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 44 MPa and the color difference b value of the optical sample was 0.7.

[0042] Example 5

[0043] 1000g of dimethyl terephthalate, 223g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 594g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide, 0.57g of triphenyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 260°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 5. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.651dL / g, a tensile strength of an injection molded sample of 45MPa, a transmittance of 93%, a haze of 0.5%, a color difference L value of 94, a value of -0.3, and an absolute value of b value of 0.6. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 44 MPa and the color difference b value of the optical sample was 0.6.

[0044] Example 6

[0045] 1000g of dimethyl terephthalate, 520g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 594g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide, 0.57g of triphenyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 6. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained, with an intrinsic viscosity of 0.648dL / g, a tensile strength of an injection molded sample of 44MPa, a transmittance of 92%, a haze of 0.6%, a color difference L value of 94, a value of -0.4, and an absolute value of b value of 0.6. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 43 MPa and the color difference b value of the optical sample was 0.7.

[0046] Example 7

[0047] 856g of terephthalic acid, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.57g of tetrabutyl titanate, 0.57g of triethyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosol were added to a reactor, and an esterification reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 7. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained, with an intrinsic viscosity of 0.650dL / g, a tensile strength of an injection molded sample of 45MPa, a transmittance of 92%, a haze of 0.5%, a color difference L value of 94, a value of -0.4, and an absolute value of b value of 0.6. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 44 MPa and the color difference b value of the optical sample was 0.6.

[0048] Example 8

[0049] 1031g of dimethyl thiophenedicarboxylate, 213g of neopentyl glycol, 596g of 1,4-cyclohexanedimethanol, 0.57g of monobutyltin triisooctanoate, 0.57g of triphenyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosol were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 8. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained with an intrinsic viscosity of 0.632dL / g, a tensile strength of an injection molded sample of 42MPa, a transmittance of 91%, a haze of 0.9%, a color difference L value of 92, a value of -0.8, and an absolute value of b value of 0.8. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 41 MPa and the color difference b value of the optical sample was 0.9.

[0050] Example 9

[0051] 887g cyclohexanedicarboxylic acid, 213g neopentyl glycol, 257g ethylene glycol, 0.57g tetrabutyl titanate, 0.57g triphenyl phosphate, 0.13g glycyrrhizic flavonoids and 0.25g carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, and the reaction was carried out at 250°C for 40min, and then evacuated to 50Pa, and the reaction was carried out at 260°C for 150min to obtain copolyester 9. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.617dL / g, a tensile strength of an injection-molded sample of 41MPa, a transmittance of 91%, a haze of 0.8%, a color difference L value of 91, a value of -0.7, and an absolute value of b value of 0.9. After the pellets were heated at 270°C for 10min, the tensile strength of the injection-molded sample was 40MPa, and the color difference b value of the optical sample was 1.0.

[0052] Example 10

[0053] 1000g of dimethyl terephthalate, 299g of isosorbide, 596g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide, 0.57g of triethyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 10. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.625dL / g, a tensile strength of an injection molded sample of 41MPa, a transmittance of 91%, a haze of 0.8%, a color difference L value of 92, a value of -0.9, and an absolute value of b value of 0.9. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 40 MPa and the color difference b value of the optical sample was 0.9.

[0054] Embodiment 11

[0055] 856g of terephthalic acid, 127g of ethylene glycol, 1258g of spirocyclic glycol, 0.57g of ethylene glycol titanium, 0.57g of triphenyl phosphate, 0.13g of glycyrrhizic flavonoids and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, and the reaction was carried out at 250°C for 40min, and then evacuated to 50Pa, and the reaction was carried out at 260°C for 150min to obtain copolyester 11. After water-cooling and pelletizing, pellets of biodegradable copolyester were obtained, with an intrinsic viscosity of 0.631dL / g, a tensile strength of an injection-molded sample of 42MPa, a transmittance of 92%, a haze of 0.8%, a color difference L value of 91, a value of -0.8, and an absolute value of b value of 0.8. After the pellets were heated at 270°C for 10min, the tensile strength of the injection-molded sample was 42MPa, and the color difference b value of the optical sample was 0.8.

[0056] Example 12

[0057] 856g of dimethyl terephthalate, 127g of ethylene glycol, 811g of tricyclodecane dimethanol, 0.57g of zinc acetate, 0.57g of triphenyl phosphate, 0.13g of glycyrrhizin and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 12. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained with an intrinsic viscosity of 0.628dL / g, a tensile strength of an injection molded sample of 42MPa, a transmittance of 91%, a haze of 0.9%, a color difference L value of 92, a value of -0.7, and an absolute value of b value of 0.9. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 41 MPa and the color difference b value of the optical sample was 1.0.

[0058] Comparative Example 1

[0059] Compared with Example 3, the only difference is that carnosic acid is not added.

[0060] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide, 0.57g of triphenyl phosphate and 0.13g of glycyrrhizin were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 13. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained with an intrinsic viscosity of 0.647dL / g, a tensile strength of an injection molded sample of 45MPa, a transmittance of 91%, a haze of 0.8%, a color difference L value of 93, a value of -0.6, and an absolute value of b value of 0.8. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 43 MPa and the color difference b value of the optical sample was 1.0.

[0061] Comparative Example 2

[0062] Compared with Example 3, the only difference is that glycyrrhiza flavonoids is not added.

[0063] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide, 0.57g of triphenyl phosphate and 0.25g of carnosic acid were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 14. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained with an intrinsic viscosity of 0.646dL / g, a tensile strength of an injection molded sample of 44MPa, a transmittance of 91%, a haze of 0.8%, a color difference L value of 93, a value of -0.6, and an absolute value of b value of 0.8. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 42 MPa and the color difference b value of the optical sample was 1.0.

[0064] Comparative Example 3

[0065] Compared with Example 3, the only difference is that carnosic acid and glycyrrhizin are not added.

[0066] 1000g of dimethyl terephthalate, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.57g of dibutyltin oxide and 0.57g of triphenyl phosphate were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 15. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained with an intrinsic viscosity of 0.647dL / g, a tensile strength of an injection molded sample of 45MPa, a transmittance of 90%, a haze of 0.9%, a color difference L value of 92, a value of -0.7, and an absolute value of b value of 0.9. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 41 MPa and the color difference b value of the optical sample was 1.2.

[0067] Comparative Example 4

[0068] Compared with Example 7, the only difference is that carnosic acid and glycyrrhizin are not added.

[0069] 856g of terephthalic acid, 295g of 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 596g of 1,4-cyclohexanedimethanol, 0.57g of tetrabutyl titanate and 0.57g of triethyl phosphate were added to a reactor, and an ester exchange reaction was carried out at normal pressure and 210°C for 150min. The reactor was then evacuated to 2kPa, reacted at 250°C for 40min, and then evacuated to 50Pa, and reacted at 260°C for 150min to obtain copolyester 16. After water-cooling and pelletizing, biodegradable copolyester pellets were obtained with an intrinsic viscosity of 0.645dL / g, a tensile strength of an injection molded sample of 45MPa, a transmittance of 90%, a haze of 0.9%, a color difference L value of 91, a value of -0.8, and an absolute value of b value of 0.8. After the pellets were heated at 270°C for 10 min, the tensile strength of the injection molded sample was 40 MPa and the color difference b value of the optical sample was 1.1.

[0070] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing a copolyester, characterized in that: The preparation method comprises the following steps: S1: esterification of a dibasic acid with a diol, and / or transesterification of a dimethyl ester of a dibasic acid with a diol to obtain an esterified product and / or a transesterified product; S2: the esterification product and / or the transesterification product are subjected to a pre-condensation reaction to obtain a prepolymer; S3: The prepolymer undergoes a final polycondensation reaction to obtain the target copolyester; Wherein, a liquorice antioxidant and a rosemary extract composition are added to S1 to carry out esterification and / or transesterification reaction.

2. The preparation method according to claim 1, characterized in that: S1 The dibasic acid or the dimethyl ester of the dibasic acid is a C6-C20 dibasic acid, preferably one or more of terephthalic acid or its dimethyl ester, isophthalic acid or its dimethyl ester, phthalic acid or its dimethyl ester, biphenyl dicarboxylic acid or its dimethyl ester, naphthalene dicarboxylic acid or its dimethyl ester, furandicarboxylic acid or its dimethyl ester, thiophenedicarboxylic acid or its dimethyl ester, cyclohexane dicarboxylic acid or its dimethyl ester, more preferably terephthalic acid or its dimethyl ester, and / or isophthalic acid or its dimethyl ester; and / or, the diol described in S1 is a C2-C20 aliphatic diol and / or aromatic diol, preferably 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, isosorbide, ethylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 1,2-propylene glycol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,4 -pentanediol, 1,5-pentanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, diethylene glycol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, spiroglycol, one or more of tricyclodecane dimethanol, more preferably 1,4-cyclohexanedimethanol and / or 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Preferably, the molar ratio of the diol to the diacid or the diester of the diacid is (1.1-1.5):1, preferably (1.2-1.4):1; And / or, the licorice antioxidant in S1 is licorice flavonoids and / or glycyrrhizin, and the rosemary extract is carnosic acid and / or carnosol; Preferably, the mass ratio of the licorice antioxidant to the rosemary extract is (0.1-10):1, preferably (0.5-3):1; Preferably, the licorice antioxidant and rosemary extract composition is 100 to 300 ppm, preferably 200 to 300 ppm, of the total mass feed amount of diol and diacid and / or diester of diacid; and / or, S1 adds a catalyst; Preferably, the catalyst is one or more of dibutyltin oxide, dimethyltin oxide, monobutyltin triisooctoate, dibutyltin dimethoxy, stannous octoate, stannous oxalate, dibutyltin diacetate, dibutyltin dilaurate, tetrabutyl titanate, isopropyl titanate, titanium glycolate, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, and manganese acetate, preferably dibutyltin oxide and / or tetrabutyl titanate; Preferably, the catalyst is 200 to 500 ppm, preferably 300 to 400 ppm, of the total mass feed amount of the diol and the diacid and / or the diester of the diacid; and / or, adding a heat stabilizer to S1; Preferably, the heat stabilizer is a phosphate compound, preferably an alkyl phosphate and / or an aryl phosphate, more preferably triphenyl phosphate and / or triethyl phosphate; Preferably, the heat stabilizer is 300 to 600 ppm, preferably 300 to 400 ppm, of the total mass feed amount of the diol and the diacid and / or the diester of the diacid; And / or, the reaction temperature of S1 is 190-240°C, preferably 210-230°C, and the reaction time is 120-240 min, preferably 150-180 min.

3. The preparation method according to claim 1, characterized in that: In the S2, the reaction temperature is 240-260°C, preferably 240-250°C, the absolute pressure of the reaction is 1-3 kPa, preferably 1-2 kPa, and the reaction time is 30-60 min, preferably 40-50 min.

4. The preparation method according to claim 1, characterized in that: In the S3, the reaction temperature is 250-270°C, preferably 260-265°C, the absolute pressure of the reaction is less than 100 Pa, preferably less than 50 Pa, and the reaction time is 120-300 min, preferably 150-210 min.

5. A copolyester, wherein the copolyester is prepared by the preparation method according to any one of claims 1 to 4, and the copolyester is a highly transparent, light-colored, heat-resistant copolyester.

6. The copolyester according to claim 5, characterized in that The intrinsic viscosity of the copolyester is greater than 0.6 dL / g, the tensile strength of the injection molded strip is greater than 40 MPa, the light transmittance of the optical sample is greater than 90%, the haze is less than 1%, and the color The difference L value is greater than 90, the absolute value of a value is less than 1, and the absolute value of b value is less than 1; after the pellets are heated at 260-280℃ for 10 minutes, The tensile strength of the injection molded strip is less than 2MPa, and the color difference of the optical sample is less than 0.2.

Citation Information

Patent Citations

  • Preparation method of transparent polyester hot melt adhesive

    CN107513362A

  • Low-crystallinity biodegradable polyester and preparation method thereof

    CN110903469A

  • Additive composition and use thereof, condensation polymer composition, molding components, molding components, molding components and molded

    CN115461396A

  • High-heat-resistance and high-transparency copolyester resin and preparation method thereof

    CN115572375A

  • Additive composition and use thereof, condensation polymer composition, molding components, molding components, molding components and molded

    CN115768825A